Combining cognitive mapping and MCDA for improving quality of life in urban areas - Faria, Patrícia A.M.; Ferreira, Fernando A.F.; Jalali, Marjan S.; Bento, Paulo; António, Nelson J.S. (Cities, 2018)
Assessing quality of life (QoL) in urban areas is considered a difficult endeavor. Some of the main reasons for this difficulty are directly related to the complexity inherent in the multiplicity of criteria that must be considered in such an evaluation, as well as the subjectivity intrinsic to the issue under study. This complexity hinders the development of models capable of reflecting the performance of different urban environments in terms of their QoL. This study sought to overcome some of the more common limitations of current evaluation methods, by combining cognitive mapping and the measuring attractiveness by a categorical based evaluation technique (MACBETH), to develop a more informed, coherent and transparent evaluation system. The resulting framework and its application were validated both by the participating panel of experts and a representative of the parliamentary group of the Portuguese ecologist party “The Greens”. The advantages and limitations of our framework are also subject of analysis and discussion. It is worth noting that the whole process assumes a constructivist stance, allowing both objective and subjective elements to be combined in the decision-making framework. •We present an MCDA framework to measure QoL in urban areas.•The approach followed overcomes some limitations of purely statistical methods.•Cognitive mapping improves variables selection and understanding.•The combined use of cognitive maps and MACBETH enhances QoL evaluation.